PENGGUNAAN MEDIA GAMBAR TERHADAP PENINGKATAN HASIL BELAJAR IPS KELAS III A DI MIN 4 SERANG - Puspitorini, Puput; Jamal, Afidah Nurfauziah (Jurnal Pendidikan Dasar Setiabudhi, 2019)
Based on the results obtained from the first cycle to the second cycle, it can be concluded that the use of image media can improve the learning outcomes of IPS students in grade III A MIN 4 Serang, the district of Pamarayan district, attack. Images of media used in this study are images of natural and artificial environments. In the learning process the image media is used in the initial activities, core activities and final activities in the first cycle, the use of picture media in social studies can improve student learning outcomes from the class average value of 65.76 to 71.92 and if using the KKM achievement value this has reached KKM. Then in the second cycle, the average value of students increased again to 76.90. This value has reached KKM and has reached a target where more than 75% of students get scores of more than 70.00. Observation results of student tolerance, from cycle I to cycle II improve gravity. This is evidenced by the increased activity of students. From this description, it can be concluded that the learning outcomes and activeness of class III MIN 4 attacks increased by using media images on social studies subjects. With media images students are increasingly eager to learn greetings in class. Keywords: The Use of Media Images, Result Learning Social Science Abstrak Berdasarkan hasil yang diperoleh dari siklus pertama ke siklus kedua, dapat disimpulkan bahwa penggunaan media gambar dapat meningkatkan hasil belajar bagi siswa di kelas III A MIN 4 Serang, kabupaten Pamarayan, serangan. Gambar media adalah gambar lingkungan alami dan buatan. Dalam proses pembelajaran, media gambar dapat digunakan untuk meningkatkan pembelajaran siswa. Hasil belajar siswa dari nilai rata-rata kelas 65,76 hingga 71,92 dan jika menggunakan nilai prestasi KKM telah mencapai KKM. Kemudian pada siklus kedua, nilai rata-rata siswa meningkat lagi menjadi 76,90. Nilai ini telah mencapai KKM dan telah mencapai target di mana lebih dari 75% siswa mendapat skor lebih dari 70,00. Hasil pengamatan toleransi siswa, dari siklus I ke siklus II meningkatkan gravitasi. Ini dibuktikan dengan meningkatnya aktivitas siswa. Dari uraian ini, dapat disimpulkan bahwa hasil dan kegiatan pembelajaran telah ditingkatkan oleh gambar media pada mata pelajaran IPS. Dengan gambar media, siswa semakin bersemangat untuk belajar salam di kelas. Kata kunci: Penggunaan Media Gambar, Hasil Belajar IPS